Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Regreening, restoring, and reconnecting a southwestern wetland ecosystem – the Zeedyk wetland - Roy E. Petrakis; Laura M. Norman; Maryann McGraw; Steve Carson; Craig Sponholtz; Cameron Weber; William D. Zeedyk (Remote Sensing Applications: Society and Environment, 2026)

Population genetic and phylogenetic analysis of pupfish (Cyprinodon, Cyprinodontidae) in the Rio Conchos and adjacent rivers reveals hidden diversity - Casey Ernest; Michael Tobler; Ma. Lourdes De Lozano-Vilano; Mauricio De La Maza-Benignos; Tracy A. Diver; Wade D. Wilson; Thomas F. Turner; Evan W. Carson (Conservation Genetics, 2026)

Inter-method differences (SIMS vs. IRMS) in oxygen isotope fractionation: insights from Chinook salmon otoliths - Kohma Arai; Malte Willmes; George E. Whitman; Kenneth W. Zillig; Cassidy J. Cooper; Nozomi Matsuda; Elizabeth A. Bell; Kevin D. McKeegan; Levi S. Lewis; Carson A. Jeffres; Rachel C. Johnson (Geochimica et Cosmochimica Acta, 2025)

Context‐dependent effects of a cryptic virus on butterfly population dynamics - Brendan D. Carson; Colin M. Orians; Elizabeth E. Crone (Ecology, 2025)
Viruses have the potential to impact host populations, but our picture of host–virus relationships is largely colored by virulent pathogens that lead to easily detectable epizootic events. Modern molecular methods have demonstrated that viruses are ubiquitous in animal populations, and the influence of these “cryptic” viruses is largely unexplored. Insects provide an ideal system to examine population‐level impacts of novel, “cryptic” viruses—short generation times allow for meaningful population‐level field studies over a relatively short timeframe, and their abundance and small size facilitate experimental manipulation across each life stage. Many insect species are capable of high population growth rates, potentially buffering them from pathogen‐driven declines in the face of high pathogen prevalence. We explored the impacts of a recently detected non‐occluded densovirus ( Junonia coenia DV, JcDV) on the demography of a nymphalid butterfly, Euphydryas phaeton (Baltimore checkerspot). E. phaeton populations are known to have the capacity for rapid growth and to exhibit large, often unexplained population fluctuations. We used a field mesocosm experiment to measure the vital rates of E. phaeton under a range of levels of viral exposure over 2 years (2021 and 2022) and used these vital rates to parameterize a demographic model of population growth in each year. We found that JcDV reduced E. phaeton post‐diapause larval survival, skewed sex ratios toward a male bias, and reduced fecundity in surviving females. JcDV reduced estimated population growth rates in both years, but only led to population decline in 2022. This increased impact was associated with a substantial regional drought, suggesting that the potential for this non‐occluded virus to cause population decline is influenced by climatic factors. The findings of our controlled study parallel trends observed in a wild population of E. phaeton , supporting the hypothesis that JcDV can drive population decline. This study demonstrates that cryptic viruses likely influence butterfly population dynamics, especially when their effects are compounded with additional environmental stressors.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

A Complicated History of Mitogenome Introgression Among Luxilus Species (Teleostei, Family Leuciscidae) in the Ozark Highlands - David D. Duvernell; Carson Arnold; Shila Koju; Abby J. Wicks; Thomas E. Dowling (Fishes, 2025)
Hybridization is common among minnows and shiners in the family Leuciscidae, and mitonuclear discordance can reveal evidence of historical hybridization and introgression events that have shaped extant species and populations. We have identified a notable case of serial mitogenome replacement in populations of two shiner species, Luxilus zonatus and L. chrysocephalus, which are syntopic in drainages throughout the northern and eastern Ozark Interior Highlands of North America. These mitogenome replacement events involved L. zonatus acquiring the mitogenome of L. chrysocephalus, and populations of L. chrysocephalus acquiring the mitogenome of an allopatric congeneric species, L. cornutus. The latter species has a more northern distribution that was likely shifted southward by glacial advances during the Pleistocene. The geographic extent of mitogenome replacements in both species spans multiple separate drainages encompassing most of the major river systems that comprise the northern and eastern Ozark Highlands. We attribute these patterns to shifting species distributions, which were impacted by multiple glacial advances and coincident geomorphological changes to Ozark Highland drainages throughout the Pleistocene. The serial nature of mitogenome replacements in L. zonatus and L. chrysocephalus may exclude a role for natural selection in these introgression events, but the dynamic shifts in species distributions and gene flow connections throughout the Pleistocene may have favored an invasion-with-hybridization model that predicts massive asymmetric introgression between invading and resident species. These results have applied significance for eDNA metabarcoding methods of biodiversity assessment in Ozark streams, as they are dependent on mitogenome detections.

Associations of volatile organic compounds with accelerated epigenetic aging in the lungs of smokers and electronic cigarette users - Ajmal Khan; Carson Richardson; Joseph P. McElroy; Amarnath Singh; Daniel Y. Weng; Sahar Kamel; Sarah A. Reisinger; Mark D. Wewers; Peter G. Shields; Min-Ae Song (Science of The Total Environment, 2025)

Caught in headlights: Captive white-tailed deer responses to variations in vehicle lighting during imminent collision scenarios - Carson J. Pakula; Gino J. D'Angelo; Adrianna Mowrer; Olin E. Rhodes; Travis L. DeVault (Applied Animal Behaviour Science, 2025)

Dynamics of hydrogen–ammonia–natural gas lean-premixed high-pressure flames - Tristan T. Shahin; Alexander J. Hodge; Benjamin K. Murdock; Thomas N. McLean; Keaton C. Koenig; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Rapid, complex back barrier pedestal formation preconditions washover deposition on the southeast Indian coast - Chris Gouramanis; Seshachalam Srinivasalu; Andasabari Karthik; Dat T. Pham; Stephen Carson; Adam D. Switzer (Marine Geology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Commercial bacteriophage preparations for the control of Listeria monocytogenes and Shiga toxin-producing Escherichia coli in raw and pasteurized milk - Emily Everhart; Sarah Carson; Kathleen Atkinson; Dennis J. D'Amico (Food Microbiology, 2025)

Influence of incorporating beta-cyclodextrin/essential oil-based wood preservative on the bonding strength of wood composite products - Hamed Olayiwola; Edward D. Entsminger; Carson Bedics; Jason T. Street; Santanu Kundu; Yunsang Kim (Carbohydrate Polymers, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A novel route of intercellular copper transport and detoxification in oyster hemocytes - Yali Luo; Aidan T. Pezacki; Carson D. Matier; Wen-Xiong Wang (Journal of Hazardous Materials, 2024)

Native tree species prosper while exotics falter during gap-phase regeneration, but only where deer densities are near historical levels - Anthony C. Yacucci; Walter P. Carson; Jenna C. Martineau; Curtis D. Burns; Brian P. Riley; Alejandro A. Royo; Thomas P. Diggins; Ian J. Renne (New Forests, 2024)

Top-down effects of intraspeciflic predator behavioral variation - James L. L. Lichtenstein; Brendan L. McEwen; Skylar D. Primavera; Thomas Lenihan; Zoe M. Wood; Walter P. Carson; Raul Costa-Pereira (Oecologia, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Effect of fuel temperature on the structure of a high-pressure liquid-fueled swirl flame - John J. Philo; Tristan T. Shahin; Colin T. McDonald; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Multiple and contrasting pressures determine intraspecific phytochemical variation in a tropical shrub - Andrea E. Glassmire; Walter P. Carson; Angela M. Smilanich; Lora A. Richards; Christopher S. Jeffrey; Craig D. Dodson; Casey S. Philbin; Garcia L. Humberto; Lee A. Dyer (Oecologia, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The obesity-breast cancer link: a multidisciplinary perspective - Emily N. Devericks; Meredith S. Carson; Lauren E. McCullough; Michael F. Coleman; Stephen D. Hursting (Cancer and Metastasis Reviews, 2022)
Obesity, exceptionally prevalent in the USA, promotes the incidence and progression of numerous cancer types including breast cancer. Complex, interacting metabolic and immune dysregulation marks the development of both breast cancer and obesity. Obesity promotes chronic low-grade inflammation, particularly in white adipose tissue, which drives immune dysfunction marked by increased pro-inflammatory cytokine production, alternative macrophage activation, and reduced T cell function. Breast tissue is predominantly composed of white adipose, and developing breast cancer readily and directly interacts with cells and signals from adipose remodeled by obesity. This review discusses the biological mechanisms through which obesity promotes breast cancer, the role of obesity in breast cancer health disparities, and dietary interventions to mitigate the adverse effects of obesity on breast cancer. We detail the intersection of obesity and breast cancer, with an emphasis on the shared and unique patterns of immune dysregulation in these disease processes. We have highlighted key areas of breast cancer biology exacerbated by obesity, including incidence, progression, and therapeutic response. We posit that interception of obesity-driven breast cancer will require interventions that limit protumor signaling from obese adipose tissue and that consider genetic, structural, and social determinants of the obesity–breast cancer link. Finally, we detail the evidence for various dietary interventions to offset obesity effects in clinical and preclinical studies of breast cancer. In light of the strong associations between obesity and breast cancer and the rising rates of obesity in many parts of the world, the development of effective, safe, well-tolerated, and equitable interventions to limit the burden of obesity on breast cancer are urgently needed.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Association Between Greater Cerebellar Network Connectivity and Improved Phonemic Fluency Performance After Exercise Training in Older Adults - Junyeon Won; Yasmeen Faroqi-Shah; Daniel D. Callow; Allison Williams; Adewale Awoyemi; Kristy A. Nielson; J. Carson Smith (The Cerebellum, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Interlimb transfer and generalisation of learning in the context of persistent failure to accomplish a visuomotor task - D. A. E. Bolton; A. R. Buick; T. J. Carroll; R. G. Carson (Experimental Brain Research, 2019)

Technological advances in maize breeding: past, present and future - Carson Andorf; William D. Beavis; Matthew Hufford; Stephen Smith; Walter P. Suza; Kan Wang; Margaret Woodhouse; Jianming Yu; Thomas Lübberstedt (Theoretical and Applied Genetics, 2019)

Dietary lipophilic iron accelerates regional brain iron-load in C57BL6 mice - Douglas G. Peters; Carson J. Purnell; Michael P. Haaf; Qing X. Yang; James R. Connor; Mark D. Meadowcroft (Brain Structure and Function, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Aflatoxin contamination in corn sold for wildlife feed in texas - Nicholas R. Dunham; Steven T. Peper; Carson D. Downing; Ronald J. Kendall (Ecotoxicology, 2017)

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Reduced white matter MRI transverse relaxation rate in cognitively normal H63D-HFE human carriers and H67D-HFE mice - Mark D. Meadowcroft; Jianli Wang; Carson J. Purnell; Douglas G. Peters; Paul J. Eslinger; Elizabeth B. Neely; David J. Gill; Megha Vasavada; Fatima Ali-Rahmani; Qing X. Yang; James R. Connor (Brain Imaging and Behavior, 2016)

Preferential binding to dopamine D3 over D2 receptors by cariprazine in patients with schizophrenia using PET with the D3/D2 receptor ligand [11C]-(+)-PHNO - Ragy R. Girgis; Mark Slifstein; Deepak D’Souza; Yih Lee; Antonia Periclou; Parviz Ghahramani; István Laszlovszky; Suresh Durgam; Nika Adham; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; et al. (Psychopharmacology, 2016)
Rationale Second-generation antipsychotics occupy dopamine D 2 receptors and act as antagonists or partial agonists at these receptors. While these drugs alleviate positive symptoms in patients with schizophrenia, they are less effective for treating cognitive deficits and negative symptoms. Dopamine D 3 receptors are highly expressed in areas of the brain thought to play a role in the regulation of motivation and reward-related behavior. Consequently, the dopamine D 3 receptor has become a target for treating negative symptoms in combination with D 2 antagonism to treat positive symptoms in patients with schizophrenia. Objective The purpose of this study was to determine the cariprazine receptor occupancies in brain for D 2 and D 3 receptors in patients with schizophrenia. Methods Using [ 11 C]-(+)-PHNO as a radioligand, positron emission tomography (PET) scans were performed in eight patients at baseline and postdose on days 1, 4, and 15. Plasma and cerebrospinal fluid (CSF) samples were analyzed for cariprazine concentrations. Results A monotonic dose-occupancy relationship was observed for both receptor types. After 2 weeks of treatment, near complete (∼100 %) occupancies were observed for both receptors at a dose of 12 mg/day. At the lowest cariprazine dose (1 mg/day), mean D 3 and D 2 receptor occupancies were 76 and 45 %, respectively, suggesting selectivity for D 3 over D 2 receptors at low doses. An exposure-response analysis found a ∼3-fold difference in EC 50 (D 3 = 3.84 nM and D 2 = 13.03 nM) in plasma after 2 weeks of dosing. Conclusion This PET imaging study in patients with schizophrenia demonstrated that cariprazine is a D 3 -preferring dual D 3 /D 2 receptor partial agonist.

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

The effects of intranasal oxytocin in opioid-dependent individuals and healthy control subjects: a pilot study - Josh D. Woolley; Peter A. Arcuni; Christopher S. Stauffer; Daniel Fulford; Dean S. Carson; Steve Batki; Sophia Vinogradov (Psychopharmacology, 2016)

Coastal sea level changes, observed and projected during the 20th and 21st century - M. Carson; A. Köhl; D. Stammer; A. B. A. Slangen; C. A. Katsman; R. S. W. van de Wal; J. Church; N. White (Climatic Change, 2016)

Projecting twenty-first century regional sea-level changes - A. B. A. Slangen; M. Carson; C. A. Katsman; R. S. W. van de Wal; A. Köhl; L. L. A. Vermeersen; D. Stammer (Climatic Change, 2014)

Recent sea level and upper ocean temperature variability and trends; cook islands regional results and perspective - D. E. Harrison; Mark Carson (Climatic Change, 2013)

Microsatellite population genetics of the emerald ash borer (Agrilus planipennis Fairmaire): comparisons between Asian and North American populations - Carson C. Keever; Christal Nieman; Larissa Ramsay; Carol E. Ritland; Leah S. Bauer; D. Barry Lyons; Jenny S. Cory (Biological Invasions, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Delivery of Water-Soluble Drugs Using Acoustically Triggered Perfluorocarbon Double Emulsions - Mario L. Fabiilli; James A. Lee; Oliver D. Kripfgans; Paul L. Carson; J. Brian Fowlkes (Pharmaceutical Research, 2010)

BACE1 Polymorphisms Do Not Influence Platelet Membrane β-secretase Activity or Genetic Susceptibility for Alzheimer’s Disease in the Northern Irish Population - S. Todd; A. J. McKnight; W. W. Liu; R. Carson; S. Heggarty; B. McGuinness; G. B. Irvine; D. Craig; A. P. Passmore; J. A. Johnston (NeuroMolecular Medicine, 2008)

Spatiotemporal distribution of heparan sulfate epitopes during murine cartilage growth plate development - Ronald R. Gomes; Toin H. Kuppevelt; Mary C. Farach-Carson; Daniel D. Carson (Histochemistry and Cell Biology, 2006)

The neurocognitive effects of aripiprazole: an open-label comparison with olanzapine - Robert S. Kern; Michael F. Green; Barbara A. Cornblatt; J. Randall Owen; Robert D. McQuade; William H. Carson; Mirza Ali; Ron Marcus (Psychopharmacology, 2006)

Hypoxia increases VEGF-A production by prostate cancer and bone marrow stromal cells and initiates paracrine activation of bone marrow endothelial cells - Caroline Muir; Leland W. K. Chung; Daniel D. Carson; Mary C. Farach-Carson (Clinical & Experimental Metastasis, 2006)

Perlecan Knockdown in Metastatic Prostate Cancer Cells Reduces Heparin-binding Growth Factor Responses in vitro and Tumor Growth in vivo - Cristiana Savorè; Chu Zhang; Caroline Muir; Riting Liu; Jeffrey Wyrwa; Jun Shu; Haiyen E. Zhau; Leland W.K. Chung; Daniel D. Carson; Mary C. Farach-Carson (Clinical & Experimental Metastasis, 2005)

QTL associations for density and diameter in Pinus radiata and the potential for marker-aided selection - M. E. Devey; S. D. Carson; M. F. Nolan; A. C. Matheson; C. Te Riini; J. Hohepa (Theoretical and Applied Genetics, 2004)

Coral‐reef sounds enable nocturnal navigation by some reef‐fish larvae in some places and at some times - J. M. Leis; B. M. Carson‐Ewart; A. C. Hay; D. H. Cato (Journal of Fish Biology, 2003)
At Lizard Island, Great Barrier Reef, catches of fish larvae by light traps that broadcast nocturnal reef sounds (noisy traps) were compared with catches by quiet traps over two 2·5 week new‐moon periods in November (XI) 2000 and January (I) 2001. Three areas were sampled: near‐reef (NR, 500 m from the shore) in I, middle (M, 650 m) in I and XI and offshore (O, >1000 m) in XI. The most abundant taxa captured were Apogonidae, Blenniidae, Chaetodontidae, Lethrinidae, Mullidae and Pomacentridae. Significant differences in catch were found between areas, and a position effect was found at the O and M areas. At the NR and M areas, no taxa had significantly greater catches in quiet traps, but larvae of five taxa had significantly greater catches in noisy traps. These were (areas and times of greater catches): Apogonidae (NR; M XI), Mullidae (M I & XI), Pomacentridae (NR; M I & XI), Serranidae (M I) and Sphyraenidae (NR). At the offshore area, five taxa (Apogonidae, Blenniidae, Chaetodontidae, Mullidae and Pomacentridae) had significantly greater catches in quiet traps and only Lethrinidae had significantly greater catches in noisy traps. Thus some taxa (particularly apogonids and pomacentrids which had catches up to 155% greater in noisy traps, but also lethrinids and mullids, and perhaps others), were attracted to reef sounds at night, but this apparently varied with location and time. The sound‐enhanced catches imply a radius of attraction of the sound 1·02–1·6 times that of the light. More than 65 m from the speaker,the broadcast sound levels at frequencies typical of fish hearing were equivalent to background levels, providing a maximum radius of sound attraction in this experiment.

Temporal and spatial distribution of paramoebae in the water column – a pilot study - G M Douglas‐Helders; D P O'Brien; B E McCorkell; D Zilberg; A Gross; J Carson; B F Nowak (Journal of Fish Diseases, 2003)
Amoebic gill disease is the main disease affecting the salmonid industry in Tasmania, but no information on the distribution of the causative pathogen, Neoparamoeba pemaquidensis , in the aquatic environment is available. This pilot study aimed to determine temporal and spatial distributions of paramoebae species in the water column, using an immuno‐dot blot technique. Water samples were collected from inside fish cages at various depths (0.5, 5.5 and 11.0 m) in both summer and winter, as well as various distances (0, 0.5, 240, 280, 750 and 1100 m) away from the sea cage and farming site. Paramoebae densities were estimated using the most probable number technique (MPN). Temperature, salinity, dissolved oxygen, turbidity, nitrite and nitrates, and bacterial counts were measured for each water sample. Data were analysed using a residual maximum likelihood test and significant associations between paramoebae densities and environmental factors were analysed. Results showed that densities were significantly higher in summer ( P = 0.017), at 5.5 m depth ( P = 0.029), and reduced to the lowest density at 1100 m away from the cage sites ( P = 0.008). Bacterial counts, turbidity and temperature were found to be significantly associated with paramoebae densities.

Wild fish are not a significant reservoir for Neoparamoeba pemaquidensis (Page, 1987) - G M Douglas‐Helders; D R Dawson; J Carson; B F Nowak (Journal of Fish Diseases, 2002)
Amoebic gill disease (AGD), caused by the protozoan Neoparamoeba pemaquidensis (Page, 1987) is the most important disease affecting salmon farms in Tasmania. Reservoirs for this protozoan parasite are largely unknown. This study investigated wild fish as a potential reservoir of N. pemaquidensis . A total of 325 wild fish, comprising 12 different fish species, were caught from and around salmon farms and examined for the presence of AGD. None of the wild fish were infected with AGD. In a laboratory trial, seahorse, Hippocampus abdominalis , greenback flounder, Rhombosolea tapirina, and Atlantic salmon, Salmo salar, were challenged with N. pemaquidensis . Neoparamoeba pemaquidensis was detected on the gills on 10 of 15 (66.7%) flounder, nine of 24 (37.5%) seahorses, and six of six (100%) Atlantic salmon. However, paramoebae positive flounder and seahorse lacked the characteristic AGD gill pathology. It is concluded that AGD does not appear in wild fish and wild fish do not seem to be a reservoir of the pathogen.

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

Genes expressed in sugarcane maturing internodal tissue - D. Carson; F. Botha (Plant Cell Reports, 2002)

Neural compensation for compliant loads during rhythmic movement - Mackey D.; Meichenbaum D.; Shemmell J.; Riek S.; Carson R. (Experimental Brain Research, 2002)

CHARACTERISTICS OF MINKE WHALE ( BALAENOPTERA ACUTOROSTRATA ) PULSE TRAINS RECORDED NEAR PUERTO RICO - David K. Mellinger; Carol D. Carson; Christopher W. Clark (Marine Mammal Science, 2000)
A bstract A nine‐day acoustic and visual survey was conducted off the West Indies in March 1994 to study the pulse trains that were detected on SOSUS arrays throughout winter in deep water between the West Indies and Bermuda. During the survey, pulse train sounds were consistently recorded in an area 190–350 km northeast of Puerto Rico. Vocalizing animals were never visually observed, but visual sighting conditions were often poor and observation height was low. Pulse trains occurred in two basic forms. The “speed‐up” pulse train was characterized by an accelerating series of pulses with energy in the 200–400 Hz band, with individual pulses lasting 40‐60 msec. Speedup pulse trains started with average pulse rates of 1.5 pulses/sec, lasted 43.7 ± 6.0 sec, and ended with average pulse rates of 2.8 pulses/sec. The less common “slow‐down” pulse train was characterized by a decelerating series of pulses with energy in the 250‐350 Hz band. Slow‐down pulse trains started at pulse rates averaging 4.5 pulses/sec, lasted 60.9 ± 5.8 sec, and ended with average pulse rates of 2.9 pulses/sec. We believe the recorded pulse trains are from minke whales based on careful reanalysis of, and comparison to, minke whale pulse‐train sounds recorded in the Caribbean by Winn and Perkins (1976).

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Genetic analysis of inbreeding depression in plus tree 850.55 of Pinus radiata D. Don. II. Genetics of viability genes - H. Kuang; T. E. Richardson; S. D. Carson; B. C. Bongarten (Theoretical and Applied Genetics, 1999)

Realized Gain and Prediction of Yield with Genetically Improved Pinus radiata in New Zealand - Susan D. Carson; Oscar Garcia; Judy D. Hayes (Forest Science, 1999)
Pinus radiata D. Don seedlots of varying genetic quality were compared in block-plot genetic-gain trials at 10 locations representing most of the site types in New Zealand. Permanent sample plots were measured annually for growth from age 6-8 yr from planting to ages 15-17 (midrotation). Seedlots from first-generation open-pollinated seed orchards and a mix of crosses that all involved the top-performing parent were, respectively, on average 4.5% and 5.3% taller and had 6% and 11% larger mean diameter, 12% and 30% more basal area, and 15% and 34% more stem volume than seedlots originating from mild mass selection in harvested stands ("climbing select"). The observed growth increases were quantified as changes in the rate of growth from that predicted by preexisting growth models in order to account for tree size and stocking differences. Seedlots from first-generation seed orchards and crosses of the top clone, respectively, grew 5.1% and 4.5% faster in height, and functions for basal area and stocking changed 13% and 26.4% faster, respectively, than the baseline growth models, which were based on climbing select. This implies that increased basal area growth must be taken into account in order to obtain accurate prediction of gain in stem volume. The incorporation of these observed increases in growth rates into stand growth models as "genetic-gain multipliers" in order to extrapolate predictions of growth of genetically improved seedlots beyond the sites, silvicultures, and seedlots represented in the genetic gain trials is discussed. For. Sci. 45(2):186-200.

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

An allele responsible for seedling death in Pinus radiata D. Don - H. Kuang; T. E. Richardson; S. D. Carson; B. C. Bongarten (Theoretical and Applied Genetics, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)